The effect of financial benefits and career paths on employee performance with tiered punishment as a moderating variable - Syarip, Nurrusly; Assa, Adrie Frans (Enrichment : Journal of Management, 2024)
The performance of WOM Finance has not yet reached optimal levels, as indicated by its total revenue trailing behind that of its competitors. Potential reasons for this shortfall could stem from suboptimal employee performance. This study aims to examine the influence of financial benefits and career advancement on employee performance, and how these influences are moderated by progressive discipline. Employing a quantitative approach with descriptive-verification analysis, the study involved 192 employees selected via proportionate stratified random sampling and utilized Structural Equation Modeling (SEM). The findings indicate that financial benefits do not significantly affect employee performance, whereas career advancement does have a significant impact. Both financial benefits and career advancement significantly influence employee performance moderated by progressive discipline. Recommendations from the study include evaluating incentive schemes, facilitating continuing education programs for employees, and reviewing disciplinary policies at PT WOM Finance.